Penggunaan Teknologi IVR untuk Meningkatkan Kinerja Dosen Praktikum - ashadi kurniawan (Faculty of Industrial Technology Universitas Islam Indonesia, 2019)
Lecturers have activities besides teaching as well as conducting research, guiding students who are in the final project, and some who get structural positions. To assist with the accuracy of the teaching process, a system to automatically remind lecturers is made, where a database is connected to the Interactive Voice Response (IVR) system. The performance of this system is tested based on the timeliness and accuracy of the lecturer room extension number contacted. Based on the results of the tests performed, the system can contact the extension number of the lecturer room registered in the database. While the delay of calls from the system to the extension number of the lecturer room reaches 5 seconds on average. So that with the system being created, it can help and expedite the teaching and learning process especially for practicum courses and also improve the performance of Practicum lecturers.